Analisis Kerugian Ekonomi Akibat Dari Hambatan Samping di JL. Yos Sudarso Cikarang Utara - Prasetyo, L B Budi (Institut Teknologi Sains Bandung, 2024)
North Cikarang District, as a Central Bussines District, has several public facilities such as train stations, traditional markets, shops, and shopping centers located on Jalan Yos Sudarso Cikarang Utara. Roadside obstacles are often related to social and economic activities, namely parking on the road body due to shops that do not provide parking spaces, public transportation facilities that drop off passengers in any place, and traffic of people to cross, which causes the road capacity to decrease. It has resulted in the Yos Sudarso Road section, which has a geometric design of a 1-lane 2-way road, becoming stagnant and causing congestion during peak hours. Congestion that occurs results in an increase in vehicle operating costs so that it can cause losses that road users in the area will receive. This study aims to determine the losses of BOK experienced by motorists on Jalan Yos Sudarso due to side obstacles and loss of time value with side obstacles. The method used in this study is quantitative data collection, which is done through surveys, field observations, and literature studies. The variables used in this study were road capacity, vehicle volume, vehicle speed, and operational vehicle costs. Data analysis techniques are used through surveys, field observations, and data evaluation. The results showed that 1) the volume of vehicles obtained during peak hours on Wednesday, 27 October 2022, occurred at 07.00-08.00 WIB with the number of vehicles of 1646 pcu/hour, 2) side obstacles that occurred on Jalan Yos Sudarso caused a decrease in road capacity from 3473 pcu/hour to 2152 pcu/hour, and 3) the value of vehicle operating cost losses (BOK) and time values due to side obstacles on Jl. Yos Sudarso amounted to Rp. 5,643,654.67/veh/hour/200m and Rp. 2,059,933,954.92/veh/year/200m